Climate, host phylogeny and the connectivity of host communities govern regional parasite assembly. Issue 1 (4th October 2017) - Clark, Nicholas J.; Clegg, Sonya M.; Sam, Katerina; Goulding, William; Koane, Bonny; Wells, Konstans
Abstract: Aim: Identifying barriers that govern parasite community assembly and parasite invasion risk is critical to understand how shifting host ranges impact disease emergence. We studied regional variation in the phylogenetic compositions of bird species and their blood parasites ( Plasmodium and Haemoproteus spp.) to identify barriers that shape parasite community assembly. Location: Australasia and Oceania. Methods: We used a data set of parasite infections from >10, 000 host individuals sampled across 29 bioregions. Hierarchical models and matrix regressions were used to assess the relative influences of interspecies (host community connectivity and local phylogenetic distinctiveness), climate and geographic barriers on parasite local distinctiveness and composition. Results: Parasites were more locally distinct (co‐occurred with distantly related parasites) when infecting locally distinct hosts, but less distinct (co‐occurred with closely related parasites) in areas with increased host diversity and community connectivity (a proxy for parasite dispersal potential). Turnover and the phylogenetic symmetry of parasite communities were jointly driven by host turnover, climate similarity and geographic distance. Main conclusions: Interspecies barriers linked to host phylogeny and dispersal shape parasite assembly, perhaps by limiting parasite establishment or local diversification. Infecting hosts that co‐occur with few related species decreases a parasite's likelihood of encountering related competitors, perhaps increasing invasion potential but decreasing diversification opportunity. While climate partially constrains parasite distributions, future host range expansions that spread distinct parasites and diminish barriers to host shifting will likely be key drivers of parasite invasions.